Abdominal Fat Depots and Subclinical Carotid Artery Atherosclerosis in Women with and without HIV Infection - Glesby, Marshall J. (J Acquir Immune Defic Syndr, 2018)
BACKGROUND: Data on associations between abdominal fat depot mass and subclinical atherosclerosis are limited, especially in women with HIV. METHODS: We assessed cross-sectional associations of dual X-ray absorptiometry scan-derived estimates of visceral adipose tissue (VAT) and abdominal subcutaneous adipose tissue (SAT) with 3 measures of subclinical carotid artery atherosclerosis-- carotid artery stiffness (Young’s modulus of elasticity), presence of carotid artery lesions, and carotid artery intima-media thickness (cIMT)-- in a subsample of participants in the Women’s Interagency HIV Study. Statistical models adjusted for demographic variables, HIV serostatus, behavioral variables, and cardiovascular risk factors. RESULTS: There were 244 women with and 99 without HIV infection (median age 42, 62% black). VAT mass (but not SAT) was associated with greater carotid artery stiffness in a fully adjusted linear regression model, including adjustment for SAT (β = 11.3 log 10(3) N*M(−2) per kg VAT, 95% confidence interval [1.0, 21.7]). Greater SAT mass was associated with lower odds of having a carotid artery lesion in a fully adjusted model, including adjustment for VAT (adjusted odds ratio, 0.49 per kg of SAT [0.25, 0.94]). Neither VAT nor SAT was associated with cIMT. The VAT/SAT ratio was not statistically associated with any of the outcomes after covariate adjustment. CONCLUSIONS: In our cross-sectional study of women, the majority of whom had HIV, greater VAT mass was associated with increased carotid artery stiffness whereas greater SAT mass was associated with a reduced odds of prevalent carotid artery lesions.